2020
DOI: 10.1038/s41598-020-59908-1
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional therapy of the primary tumour in de novo stage IV breast cancer in 216 066 patients: A meta-analysis

Abstract: Patients presenting with de novo stage IV metastatic breast cancer have a complex disease which is normally treated with palliative intent and systemic therapy. However, there is mounting evidence that resection of the primary tumour and/or localised radiotherapy (locoregional therapy; LRT) could be associated with overall survival improvements. We aimed to conduct a meta-analysis to inform decision making. Using the PubMed, Cochrane and Ovid SP databases, a literature review and meta-analysis were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 62 publications
2
42
0
3
Order By: Relevance
“…Stage IV BC patients aged 70e79 years, with poorly differentiated or undifferentiated tumor, with lymph node-positive disease, who received chemotherapy, with TNBC, with married status, or with a history of benign or borderline tumors were more likely to receive LRT, which is consistent with the results of multiple retrospective analyses that patients who choose surgery may be younger, have a higher histological grade, and have fewer metastases or only have bone metastases [13]. After adjusting for confounding factors, the prognosis of the surgery group was better than that of the non-surgery group (OS, HR ¼ 0.751, 95% CI [0.668e0.843], P < 0.001.…”
Section: Discussionsupporting
confidence: 81%
“…Stage IV BC patients aged 70e79 years, with poorly differentiated or undifferentiated tumor, with lymph node-positive disease, who received chemotherapy, with TNBC, with married status, or with a history of benign or borderline tumors were more likely to receive LRT, which is consistent with the results of multiple retrospective analyses that patients who choose surgery may be younger, have a higher histological grade, and have fewer metastases or only have bone metastases [13]. After adjusting for confounding factors, the prognosis of the surgery group was better than that of the non-surgery group (OS, HR ¼ 0.751, 95% CI [0.668e0.843], P < 0.001.…”
Section: Discussionsupporting
confidence: 81%
“…As seen in other studies, the authors conclude that the treatment plans should be made in a multidisciplinary setting with LRT being strongly considered for select group of patients with favorable prognostic factors. Most recently, Gera et al 14 in 2020 published the largest meta-analysis regarding the question of LRT in de novo stage IV setting. This study showed that LRT resulted in significant 31.8% reduction in mortality, HR = 0.6823.…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain this benefit, such as the disruption of self-seeding of the primary tumour, cancer stem cell elimination and overall reduction tumour burden. [37][38][39][40] Tumour manipulation can also lead to tumour cell destruction and releasing tumour-associated antigens into circulation, improving immune response by an abscopal effect. 41 As 57.5% of cats had local mammary disease at diagnosis and 12% of cats developed new mammary tumours and/or local metastatic disease after the diagnosis, local resection may be suggested and necessary to improve the quality of life, especially in ulcerated and aggressive local disease.…”
Section: Discussionmentioning
confidence: 99%